Riparian Plant and Fish in Klampok Swamp, Senggreng Village, Malang District, East Java - Arfiati, Diana; Zakiyah, Umi; Anitasari, Septi; Prabandani, Alfurena; Orchida, Kharisma; Inayah, Zakiyyah Nur; Pratiwi, Rizky Kusma (Faculty of Fisheries and Marine Science, Brawijaya University, Malang, Indonesia, 2024)
Riparians vegetation can improve water quality, feeding grounds, spawning grounds, nursery grounds, and shelter grounds for fish. The aim of this research is to determine the types of riparian plants, types of fish and water quality in Klampok Swamp, Senggreng Village, Malang Regency, East Java. This research was conducted using the survey method to determine the types of riparian plants, types of fish, and water quality in Klampok Swamp, Senggreng Village, Malang Regency, East Java. The data is taken from 4 stations determined by the riparian cover. The station I with 100% riparian cover, station II (70%), station III (40%), and station IV (5%). The fish obtained from the research results in Klampok Swamp are betta fish (Osphronemidae), blue panchax (Aplocheilidae), snakehead (Channidae), marble goby (Eleotridae), guppy (Poeciliidae) or million fish, tilapia and the red devil (Cichlidae), goby fish and transparent goby fish (Gobiidae). Found 14 families of riparian, with the most species being Asteraceae (7 species of cosmos). The families in all stations are Poaceae or grains and Amaranthaceae (spinach). Water quality indicates waters that are good for fish and other organisms.